Comparing the application of three thrombosis risk assessment models in patients with acute poisoning: A cross-sectional survey - Wen, Zixin; Li, Xiuqin; Zhang, Yanxia; Shi, Jie; Zhang, Juan; Zheng, Yingying; Lin, Ying; Jian, Tianzi; Jian, Xiangdong; Kan, Baotian; Luan, Xiaorong (Frontiers in Medicine, 2022)
Background Patients with acute toxic hemoperfusion are prone to deep vein thrombosis. However, there is no risk assessment model for thrombosis in patients with acute toxic hemoperfusion. Therefore, we compared three commonly used risk assessment models for deep vein thrombosis to determine the model most suitable for assessment of deep vein thrombosis in patients with acute toxic hemoperfusion. Methods Caprini, Autar, and Padua thrombosis risk assessment models were used to assess the risk of deep vein thrombosis in patients with acute poisoning and hemoperfusion admitted to a grade A hospital in Shandong province from October 2017 to February 2019. The predictive values of the three models were compared using receiver operating characteristic (ROC) curve analysis. Results The risk assessment model scores of Caprini, Autar, and Padua were 7.55 ± 1.76, 8.63 ± 2.36, and 3.92 ± 0.55, respectively. The Caprini risk assessment model was significantly different (p < 0.05) in high-risk patients in the thrombus and non-thrombotic groups; the difference between the other two models was not significant (p > 0.05). The areas under the ROC curve of the Caprini, Autar, and Padua risk assessment models were 0.673, 0.585, and 0.535, respectively. The difference in areas under the ROC curve between the Caprini risk assessment model and the Autar risk assessment model as well as the Padua risk assessment model was significant (p < 0.05), but the areas under the ROC curve of the Autar risk assessment model and the Padua risk assessment model were not statistically significant (p > 0.05). The Caprini risk assessment model had a sensitivity of 91.9%, specificity of 33.1%, and a Youden index of 0.249. The sensitivity and specificity of Autar’s risk assessment model were 37.0 and 77.2%, respectively, and the Youden index was 0.141. The Padua risk assessment model had a sensitivity of 91.3%, specificity of 15.0%, and a Youden index of 0.063. Conclusion The three thrombosis risk assessment models were not suitable for patients with acute poisoning and hemoperfusion.